Heart rate variability and hormone replacement therapy - Christ, Michael; Seyffart, Karen; Tillmann, Hanns-Christian; Wehling, Martin (The lancet, 1999)
To compare the effects of a daily oral 1-mg dose of continuous 17β-estradiol (E2) plus intermittent (3 days off, 3 days on) norgestimate (NGM) 90 μg (n = 221), an oral 2-mg dose of continuous E2 plus intermittent NGM 180 μg (n = 219), and an oral 2-mg dose of continuous E2 plus continuous norethisterone acetate (NETA) 1 mg (n = 217) on blood lipids and lipoproteins in postmenopausal women. - The present study was undertaken because some progestins have adverse effects on lipid profiles, thereby negating the favorable effects of estrogens. Methods: This was a multicenter, randomized, parallel-group trial that focused primarily on the 2 marketed regimens—E2 1 mg/NGM 90 μg and E2/NETA. Both subjects and investigators were blinded to the intermittent regimens, the continuous combined regimen was administered open-label. After a minimum 12-hour overnight fast, blood samples were collected at baseline and during months 7 and 12 to determine lipid and lipoprotein concentrations using validated methods. - E2 1 mg/NGM 90 μg was associated with significant (ie, the 95% CI did not include 0) increases in high-density lipoprotein cholesterol (HDL-C) (6.8% [95% CI = 4.7%, 9.0%]and 4.8% [2.3%, 7.2%]at months 7 and 12, respectively) and high-density lipoprotein 2 cholesterol (HDL2-C) (10.8% [6.2%, 15.3%]and 24.1% [18.9%, 29.4%]) concentrations, and decreases in total cholesterol (−7.7% [−9.0%, −6.3%]and −9.2% [−10.5%, −7.9%]), low-density lipoprotein cholesterol (−14.3% [−16.3%, −12.4%]and −14.9% [−16.7%, −13.2%]), and lipoprotein(a) (−30.6% [−41.4%, −20.0%]at month 12) concentrations. A significant difference (P < 0.001 by analysis of variance) between the E2 1 -mg/NGM 90-μg and NETA regimens was seen for HDL-C and HDL2-C concentrations, which were elevated in subjects receiving E2 1 mg/NGM 90 μg but reduced (−9.1% [−11.1%, −7.1%]and −12.3% [−14.3%, −10.3%]for HDL-C at months 7 and 12, respectively; −14.2% [−18.0%, −10.4%]and −2.5% [−7.8%, +2.8%]for HDL2-C at months 7 and 12, respectively) in those receiving E2/NETA. - In the present study, continuous E2 1 mg/NGM 90 μg was associated with beneficial effects on lipids and hpoproteins in healthy postmenopausal women, effects that were greater at least for HDL-C and HDL2-C than those observed with continuous combined E2/NETA. The applicability of the study results to women with preexisting cardiovascular disease or dyshpidemia, or those who are overweight, remains to be investigated.
Elektronische Reproduktion der Druck-Ausgabe 7. April 2005
Gesehen am 13.10.2022